New variety of sweet potato (Ipomoea batatas L. Lam.) with better agronomic and commercial characteristics - Cantoral, Eladio (2020)
The objective of this study was to determine the agronomic and economic value of a new sweet potato (Ipomoea batatas L. Lam.) clone proposed as a commercial variety. For this purpose, the following evaluations were carried out: (1) parental crossing, seed sowing in greenhouse and seedling transplantation in a mesh house, (2) field performance assessment and (3) plot validation (profitability analysis).  root yield (t ha-1), viral detection, pulp color, plant vigor, weight loss during storage, cooking, sweetness, moisture percentage, dry matter, fat, raw fiber, carbohydrates and proteins, amount of soluble solids (Brix degrees), carotenoids (µg β-CE g-1) and antioxidant activity with ABTS radical (µmol TE g-1) were evaluated. It was demonstrated that the clone 54, named as INIA 329-Bicentenario, was agronomically and economically better than the commercial variety Amarillo Benjamín, used as a control group. The clone 54 showed viral resistance and better commercial features such as higher yield (3.0 t ha-1 of additional yield), better shape, size and pulp color, faster cooking. Moreover, the clone 54 was sweeter, and had lower fat content and a longer shelf life. Thus, the clone 54 showed higher profitability and lower risk for the farmers.